Syntaxonomic synopsis of the forest and tall scrub vegetation of Northern Algeria - Meddour, Rachid; Meddour-Sahar, Ouahiba; Zeraia, Lamri; Mucina, Ladislav (Lazaroa, 2017)
This paper presents the first syntaxonomic conspectus of the forest and scrub communities of Northern Algeria. The communities belong mainly to the zonal classes such as the Quercetea ilicis, Quercetea pubescentis and Junipero-Pinetea sylvestris (new to Algeria). The azonal vegetation is represented by four classes: Alno glutinosae-Populetea albae, Salicetea purpureae, Alnetea glutinosaeFranguletea (the latter being recognized in Algeria for the first time). We attempted to include all known syntaxa as featured in both regular and grey literature; many of those still await effective publication or formal validation. The paper also presents formal descriptions (and/or validations) of one new order, 12 new alliances, and 15 new associations.